2010
DOI: 10.1155/2010/427694
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Monocarboxylate Transporters 1, 2, and 4 in Human Tumours and Their Association with CD147 and CD44

Abstract: Monocarboxylate transporters (MCTs) are important cellular pH regulators in cancer cells; however, the value of MCT expression in cancer is still poorly understood. In the present study, we analysed MCT1, MCT2, and MCT4 protein expression in breast, colon, lung, and ovary neoplasms, as well as CD147 and CD44. MCT expression frequency was high and heterogeneous among the different tumours. Comparing with normal tissues, there was an increase in MCT1 and MCT4 expressions in breast carcinoma and a decrease in MCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
136
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 147 publications
(146 citation statements)
references
References 40 publications
10
136
0
Order By: Relevance
“…Previous studies have found greater ENT1 mRNA expression in breast cancer than in cancer cell lines derived from stomach cancer (Lu et al, 2002;Kameyama et al, 2011). Immunohistochemical analysis showed that the frequency of MCT1 expression was greater in human stomach cancer tissues than in breast cancer tissues (Pinheiro et al, 2009(Pinheiro et al, , 2010. These transporter expression profiles are consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have found greater ENT1 mRNA expression in breast cancer than in cancer cell lines derived from stomach cancer (Lu et al, 2002;Kameyama et al, 2011). Immunohistochemical analysis showed that the frequency of MCT1 expression was greater in human stomach cancer tissues than in breast cancer tissues (Pinheiro et al, 2009(Pinheiro et al, , 2010. These transporter expression profiles are consistent with the present results.…”
Section: Discussionsupporting
confidence: 92%
“…49 Immunohistochemistry for MCT4, GLUT1, and CAIX was performed according to the streptavidin-biotin-peroxidase complex principle (Ultravision Detection System Anti-polyvalent, HRP, Thermo Scientific, #TP-125-HL), as previously described. [50][51][52] Specificity of the antibodies was previously validated by siRNA followed by Western-blot. 53,54 Negative controls were performed by the use of appropriate serum controls for the primary antibodies (Dako, #N1698 and #N1699).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Both MCT1 and MCT4 were found in cancer cells, closely associated with CD147, also known as Extracellular Matrix Metalloproteinase Inducer (EMMPRIN) or basigin, a chaperone needed for the correct targeting of MCT1 and MCT4 to the cell surface and for their activity (Izumi et al 2003;Halestrap 2011;Nabeshima et al 2006;Riethdorf et al 2006;Hussien and Brooks 2011;Kirk et al 2000;Wilson et al 2005). Although these transporters are present in the plasma membrane of normal cells, there is evidence for their upregulation in cancer cells, given the increased lactic acid production and consequent efflux by the cell (Froberg et al 2001;Fang et al 2006;Pinheiro et al 2008a;Pinheiro et al 2008b;Pinheiro et al 2010a;Pinheiro et al 2010b). Tumor cells take up or export lactate according to the oxygen availability, lactate concentration and expression of the MCT subtype at the plasma membrane (Brooks 2000;Semenza 2008).…”
Section: Introductionmentioning
confidence: 99%